1996
DOI: 10.1097/00005537-199601000-00008
|View full text |Cite
|
Sign up to set email alerts
|

“Decadose” Effects of Cisplatin on Squamous Cell Carcinoma of the Upper Aerodigestive Tract. II. Clinical Studies

Abstract: There is evidence that solid tumors rapidly acquire cellular resistance to cisplatin. This resistance is usually mild to moderate and could be circumvented with higher concentrations of drug exposure if ancillary methods were available to avoid systemic cytotoxicity. The purpose of this study was to determine whether a tenfold increase in dose (decadose) would overcome cisplatin resistance. In a clinical trial, response effects of cisplatin at dose intensities ranging from 32.5 to 200 mg/m2 per week, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 21 publications
1
18
0
2
Order By: Relevance
“…Robbins et al (44) clinically investigated whether a drugresistant tumour remains resistant even for high doses of cisplatin through a tenfold increase in the administered dose. The doses used in this trial ranged from 32.5 to 200 mg/m 2 per week, and to overcome toxicity, cisplatin was delivered by intra-arterial infusion with simultaneous intravenous administration of sodium thiosulphate as a neutralizing agent.…”
Section: Chemoresistance and Radioresistancementioning
confidence: 99%
“…Robbins et al (44) clinically investigated whether a drugresistant tumour remains resistant even for high doses of cisplatin through a tenfold increase in the administered dose. The doses used in this trial ranged from 32.5 to 200 mg/m 2 per week, and to overcome toxicity, cisplatin was delivered by intra-arterial infusion with simultaneous intravenous administration of sodium thiosulphate as a neutralizing agent.…”
Section: Chemoresistance and Radioresistancementioning
confidence: 99%
“…The same group went on to expand their observations suggesting that resistance to standard doses of cisplatin could be overcome substantially with supradose cisplatin therapy delivered interarterially. 35 High-dose IA cisplatin subsequently was incorporated into a multimodality treatment plan with concomitant RT 36 ; the CR rate was 80% at the level of the primary tumor and 61% regionally, the projected 5-year OS rate was 39%, and the diseaserelated survival rate was 54%. This approach was adopted by the Radiation Therapy Oncology Group, with a reported CR rate of 86% at the primary site and 89% regionally; and, with a median follow-up of 18.4 months, the 2-year local control rate was of 62% and the survival rate was 58%.…”
Section: Discussionmentioning
confidence: 99%
“…The observed response rates in that study suggested that acquired tumor resistance to cisplatin may be overcome through the use of these very high concentrations, with an 86% response in previously untreated patients (CR rate, 45%; partial response [PR] rate, 41%) and a 63% response rate in patients with recurrent disease (CR rate, 25%, PR rate, 38%). The patients who responded to treatment were subsequently found to have received a significantly higher average dose intensity than nonresponders (120.7 vs. 57.8 mg/m 2 per week; p = .031), suggesting that high tumor response rates can be achieved through the incorporation of decadose cisplatin therapy into multimodality treatment plans [8].…”
Section: Study Outcomesmentioning
confidence: 99%
“…It was previously demonstrated in vitro [7] and in vivo [8] that resistance may be overcome through the use of higher concentrations of cisplatin. However, in human subjects, the higher concentrations required could lead to devastating systemic toxicity-already a major problem with chemoradiation protocols, which also appear to aggravate radiation-induced mucositis [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation